Reverberation Time Analysis in the Makassar Grand Mosque - Moh.Eran; Asniawaty Kusno; Nurul Jamala (Journal of Architectural Research and Design Studies, 2022)
Mosque as a place of worship for Muslims demands to provide the maximum comfort for its users to make worship more solemn. In fact, many mosques do not pay attention to the comfort of the room, including the acoustic design. This research was conducted using I-SIMPA software, a software used to perform acoustic simulations involving geometric and acoustic parameters on architectural elements in the room with the aim of analyzing the reverberation level in the Makassar Grand Mosque space. The result obtained from analysis on the first floor shows the lowest reverberation time (RT) for 1.13 seconds at points 5, 6, and 8 at 8000 Hz. Moreover, the highest RT is 4.1 seconds at point 5 at 250 Hz and points 2 and 6 at 500 Hz which is exceeds the standard of recommended RT. On the second floor, The lowest RT is 1.38 seconds at point 1 at 8000 Hz and the highest is 4.86 seconds at point 3 at 1000 Hz. The reverberation time in second floor is longer compared to the first floor due to the volume and shape of the room. Keywords: acoustics performance, accoustic simulation, I-SImpa, Mosque room, reverberation time